Exploration of Elite Stilbene Synthase Alleles for Resveratrol Concentration in Wild Chinese Vitis spp. and Vitis Cultivars - Zheng, Xianbo; Shi, Jiangli; Yu, Yinmei; Shen, Yanlong; Tan, Bin; Ye, Xia; Li, Jidong; Feng, Jiancan (Frontiers in Plant Science, 2017)
Resveratrol contributes to a plant’s tolerance of various abiotic and biotic stresses and is highly beneficial to human health. A search for elite alleles affecting resveratrol production was undertaken to find useful grapevine germplasm resources. Resveratrol levels in both berry skins and leaves were determined in 95 grapevine accessions (including 50 wild Chinese grapevine accessions and 45 cultivars) during two consecutive years. Resveratrol contents were higher in berry skins than in leaves and in wild Chinese grapevines than in grapevine cultivars. Using genotyping data, 79 simple sequence repeat (SSR) markers linked to 44 stilbene synthase (STS) genes were detected in the 95 accessions, identifying 40 SSR markers with higher polymorphisms. Eight SSR marker loci, encompassing 19 alleles, were significantly associated with resveratrol content on (P<0.001), and 5 SSR loci showed repeated associations. Locus Sh5 had four associations: three positive for allele 232 (including leaves in the two years) and one negative for allele 236 in four environments. Loci Sh9 and Sh56 for a total of 7 alleles exhibited positive effects in berry skins in the two years. In berry skins, locus Sh56 with positive effects was closely linked to VvSTS27, and locus Sh77 with negative effects to VvSTS17, importantly, the two candidate genes both were located on Chromosome 16. The SSR marker loci and candidate genes identified in this study will provide a useful basis for future molecular breeding for increased production of natural resveratrol and its derivatives.